Verbal and gender conflict - Ouhssou, Youssef; Ali, Fallous (Interacción y Perspectiva, 2023)
Interaction among users of social media is constantly multiplying, creating a fertile space for exchange between opposing positions. Indeed, each user expresses his or her point of view on a given theme, provoking the reaction of one or more digital inter-actors. We find ourselves faced with a digitized issue, giving rise to supporters and opponents who defend themselves individually or collectively, generating attacks, counter-attacks, insults and name-calling. The gender question on a national and/or international scale highlights a conflict between the radically feminist and the absolutely anti-feminist, a polemic that seeks to attribute absolute power to one of the two genders in the form of a gender battle. Instead of focusing on social, economic and cultural development, some people insist on the gender that is capable of achieving such development, which calls into question the specificity of the discourse employed by each of the two clans in terms of influence and manipulation. At this level, we will try to decode the speech acts performed by some users of the Facebook platform, Instagram and Whatsapp with the aim of  interpreting the reasons, references and factors that led each of them to opt for certain opinions. We tried to conduct a cognitive-pragmatic analysis of the speech acts accomplished by the representative sample, moreover, we distributed a questionnaire to around forty people in order to better interpret the conversational attitudes of the uses.